Metal-silane composite catalyst as well as preparation method and application thereof
By using metal-silane composite catalyst, the problems of insufficient activity of existing catalysts and high oligomer content are solved, and olefin polymerization catalysts with high activity, low hexane extract and low oligomer are achieved, thereby improving the performance and processing performance of the polymer.
Patent Information
- Application Number
- CN202311189055.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-14
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2043-09-14
AI Technical Summary
The existing catalysts are not active enough in olefin polymerization, have insufficient melting index, and have a high oligomer content in the polymer, which affects the performance and processing performance of the product.
A metal-silane composite catalyst is used, which consists of diazepinyl dialkoxysilane compounds, organic compounds containing C-O and/or C=O, metal halides and ultrafine inorganic oxides, and is prepared by stirring reactions and spray drying, and is used in combination with organic aluminum compounds.
The activity and melt index of the catalyst are significantly improved, the content of hexane extract and oligomer is reduced, and the performance and processing properties of the polymer are improved.
Smart Images

Figure BDA0004451308160000111
Abstract
Description
Technical Field
[0001] The invention belongs to the field of catalysts, and specifically relates to a metal-silane composite catalyst and a preparation method thereof, and an olefin polymerization catalyst prepared by using the metal-silane composite catalyst and used in olefin polymerization reactions. Background Art
[0002] The catalyst components will affect the performance of the polymer in the homopolymerization or copolymerization of olefins. The catalyst will produce some oligomers while catalyzing the polymerization of ethylene. The oligomers change the stress conditions between polyethylene molecules, affecting the performance and processing properties of the product, and affecting the yield strength, elongation and rigidity of the product. The amount of oligomers is generally measured by the amount of hexane extracts, so the amount of hexane extracts is also an important indicator for measuring catalyst performance.
[0003] Chinese patent CN101173015A provides a catalyst component for ethylene polymerization or copolymerization, which is a titanium-containing solid, and loaded with at least one transition metal titanium compound and at least one electron donor compound. It is characterized in that it is a titanium-containing solid, and loaded with at least one transition metal titanium compound and at least one electron donor compound; the general formula of the transition metal titanium compound is Ti(OR) a X b , wherein R is a C1-C14 aliphatic hydrocarbon group or an aromatic hydrocarbon group, X is a halogen, a is an integer from 0 to 2, b is an integer from 0 to 4, and a+b=3 or 4; the electron donor compound is selected from aliphatic ethers, cycloaliphatic ethers or aliphatic ketones. It has the characteristics of high catalytic ethylene polymerization activity, strong copolymerization ability, high polymer bulk density, and less subdivision, and is suitable for ethylene slurry polymerization or gas phase polymerization. However, the catalyst generates more fine powder in industrial applications, which is not conducive to the operation of the device.
[0004] Chinese patent CN100389134A provides a catalyst component for ethylene polymerization or copolymerization, which comprises a solid containing magnesium / titanium, loaded with at least one transition metal titanium compound, at least one suitable electron donor, and at least one hydrogen adjustment performance improver. The catalyst containing the catalyst component has the characteristics of particularly good hydrogen adjustment sensitivity, high catalytic activity, good catalyst and polymer particle morphology, low fine powder content, etc., and is very suitable for ethylene slurry and gas phase polymerization processes, especially for the production process of producing ethylene polymers with wide molecular weight distribution using dual reactors. It is characterized in that it comprises a catalyst component obtained by loading at least one transition metal titanium compound, at least one electron donor and at least one hydrogen adjustment performance improver on a solid containing titanium / magnesium; the electron donor is aliphatic ether, aromatic ether, cycloaliphatic ether and aliphatic ketone; the general formula of the transition metal titanium compound is Ti(OR) a Xb , wherein R is a C1-C14 aliphatic hydrocarbon group or an aromatic hydrocarbon group, X is a halogen atom, a is an integer from 0 to 2, b is an integer from 0 to 4, and a+b=3 or 4; the hydrogen adjustment performance improver is silicon tetrachloride. This solution reduces the oligomer content in the polymer, but the activity of the catalyst is not high enough.
[0005] Chinese patent CN112812205A discloses a catalyst component for olefin polymerization, a catalyst, a preparation method and an application thereof, which are particularly suitable for gas phase fluidized bed process. The catalyst component includes catalyst component 1 and catalyst component 2; wherein catalyst component 1 contains: 1) an ultrafine inorganic oxide carrier, and 2) a reaction and coordination product of a magnesium halide, a titanium halide, an electron donor compound and a nitrogen-oxygen heterocyclic compound; catalyst component 2 is a heterocyclic compound containing S atoms. The catalyst comprises the reaction product of the following components: (A) the catalyst component of the present invention; and (B) a catalyst component of the general formula AlR d X 3-d The catalyst of the present invention shows high activity in the field of gas phase polymerization, the obtained polymer has higher bulk density, and more importantly, has good copolymerization performance, which provides a basis for improving the production stability of the gas phase fluidized bed and the development of new products.
[0006] Therefore, there is an urgent need to develop a catalyst for olefin polymerization with higher activity and melt index and low oligomer content in the polymer. Summary of the invention
[0007] In view of the shortcomings of the prior art, the present invention provides a metal-silane composite catalyst for olefin polymerization. The composite catalyst component contains ultrafine inorganic oxides and a main catalyst component, wherein the main catalyst component is a metal-silane complex obtained by reacting a diazaheterocyclic dialkoxysilane compound, an organic compound containing CO and / or C=O, and a metal halide. After the composite catalyst component and an organic aluminum compound are activated, the catalyst is used for olefin polymerization.
[0008] One of the purposes of the present invention is to provide a metal-silane composite catalyst, comprising: a diazacyclodialkoxysilane compound, an organic compound containing CO and / or C=O, a mixture of metal halides and / or the reaction product of the above components, wherein the metal halide comprises titanium halide and magnesium halide.
[0009] According to the present invention, in the metal-silane composite catalyst:
[0010] The general formula of the diazaheterocyclic dialkoxysilane compound is (RO) 2 Si(NC n H 2n )2 , where -NC n H 2n is a nitrogen heterocyclic group, n is an integer of 3 to 10, preferably 4 or 5; R is selected from C1 to C8 alkyl, C2 to C6 alkenyl, C2 to C6 alkynyl, C3 to C10 cycloalkyl or C6 to C12 aryl, preferably C1 to C5 alkyl, C3 to C8 cycloalkyl or C6 to C10 aryl; specifically, the diazaheterocyclic dialkoxysilane compound is selected from at least one of dipiperidyldiethoxysilane, dipiperidyldimethoxysilane and dipyrrolyldiethoxysilane;
[0011] The organic compound containing CO and / or C=O is selected from at least one of esters, ethers, and ketones, preferably at least one of alkyl esters of C1-C8 saturated fatty carboxylic acids, alkyl esters of C7-C12 aromatic carboxylic acids, C2-C10 fatty ethers, C3-C8 cyclic ethers, and C3-C8 saturated fatty ketones; specifically, the organic compound containing CO and / or C=O is selected from at least one of methyl formate, ethyl formate, isopropyl formate, n-propyl formate, methyl acetate, ethyl acetate, n-propyl acetate, isopropyl acetate, n-butyl acetate, isobutyl acetate, ethyl ether, propyl ether, hexyl ether, tetrahydrofuran, acetone, and methyl isobutyl ketone, preferably at least one of methyl formate, ethyl acetate, n-butyl acetate, ethyl ether, hexyl ether, tetrahydrofuran, acetone, and methyl isobutyl ketone, more preferably tetrahydrofuran;
[0012] The magnesium halide may be a common magnesium halide compound, for example, the magnesium halide is selected from at least one of magnesium chloride, magnesium bromide, and magnesium iodide;
[0013] The titanium halide may be a common titanium halide compound, for example, the titanium halide is selected from at least one of titanium trichloride, titanium tetrachloride, titanium tribromide, and titanium tetrabromide, preferably at least one of titanium trichloride and titanium tetrachloride;
[0014] The metal-silane composite catalyst also includes ultrafine inorganic oxides. Specifically, the ultrafine inorganic oxide is selected from at least one of ultrafine alumina and ultrafine silica, preferably ultrafine silica; the particle size of the ultrafine inorganic oxide is 0.01 to 10 μm, preferably 0.01 to 5 μm, and more preferably 0.01 to 2 μm; based on the total weight of the metal-silane composite catalyst as 100 wt%, the ultrafine inorganic oxide is 5 to 40 wt%, preferably 10 to 35 wt%, and more preferably 15 to 30 wt%.
[0015] According to the present invention, in the metal-silane composite catalyst:
[0016] Based on the total weight of the metal-silane composite catalyst being 100 wt%, the content of titanium element is 0.2 to 5.5 wt%, preferably 0.5 to 3.0 wt%, and more preferably 1.8 to 2.5 wt%;
[0017] Calculated per mol of titanium element, the diazacyclodialkoxysilane compound is 0.02 to 12 mol, preferably 0.1 to 10 mol, and more preferably 0.1 to 5 mol; the organic compound containing CO and / or C=O is 1 to 550 mol, preferably 25 to 350 mol, and more preferably 120 to 250 mol; the magnesium halide is 0.3 to 12 mol, preferably 1 to 10 mol, and more preferably 1 to 8 mol.
[0018] The second object of the present invention is to provide a method for preparing the above-mentioned metal-silane composite catalyst, comprising: reacting components including a diazaheterocyclic dialkoxysilane compound, an organic compound containing CO and / or C=O, and a metal halide to obtain the above-mentioned metal-silane composite catalyst.
[0019] According to the present invention, the preparation method of the metal-silane composite catalyst specifically comprises the following steps:
[0020] (a) stirring and reacting the components including the diazaheterocyclyldialkoxysilane compound, the organic compound containing CO and / or C=O, the titanium halide and the magnesium halide to obtain a composite catalyst mother liquid;
[0021] (b) adding the ultrafine inorganic oxide to the composite catalyst mother solution and mixing to obtain a slurry;
[0022] (c) spray drying the slurry to obtain the metal-silane composite catalyst.
[0023] According to an embodiment of the present invention, in the method for preparing the metal-silane composite catalyst:
[0024] The reaction conditions in step (a) are: reaction temperature is 55-85° C., and reaction time is 2-3.5 h;
[0025] The ultrafine inorganic oxide in step (b) can be added to the composite catalyst in a solid form or in a dispersed liquid form, such as commercially available silica gel;
[0026] The content of the ultrafine inorganic oxide in step (b) is such that after mixing with the mother liquid, a slurry suitable for spray drying is formed. Preferably, the content of the ultrafine inorganic oxide in the slurry is 1 to 45 wt %, preferably 5 to 30 wt %;
[0027] The spray drying in step (c) can adopt the spray drying equipment and spray drying conditions commonly used in the prior art. Specifically, the spray drying conditions include: an inlet temperature of 90 to 220°C, preferably 110 to 200°C; an outlet temperature of 70 to 110°C, preferably 95 to 110°C.
[0028] The third object of the present invention is to provide the above-mentioned metal-silane composite catalyst or the metal-silane composite catalyst obtained by the above-mentioned preparation method for preparing an olefin polymerization catalyst.
[0029] A fourth object of the present invention is to provide an olefin polymerization catalyst, comprising: an organic aluminum compound, and the above-mentioned metal-silane composite catalyst or the metal-silane composite catalyst obtained by the above-mentioned preparation method.
[0030] According to the present invention, in the olefin polymerization catalyst:
[0031] The general formula of the organoaluminum compound is A1R n X 3-n , wherein R is a C1-C18 straight or branched alkyl group, X is a halogen, and 0<n≤3; preferably, the organoaluminum compound is selected from at least one of triethylaluminum, triisobutylaluminum, tri-n-hexylaluminum, tri-n-octylaluminum, and diethylaluminum monochloride;
[0032] The molar ratio of the aluminum element in the organic aluminum compound to the titanium element in the metal-silane composite catalyst is (3-4500):1, preferably (12-1800):1.
[0033] In order to make the solid catalyst component obtained after spray drying suitable for the production of ethylene polymers, the organic aluminum compound as the activator component must reduce the titanium atoms in the catalyst component to a state that can effectively polymerize ethylene. Generally, the above-mentioned catalyst component and the activator component are reacted in a hydrocarbon solvent to obtain a catalyst that can polymerize olefins; or the above-mentioned catalyst component and the activator component are reacted in a hydrocarbon solvent during the polymerization process to further induce olefin polymerization. The hydrocarbon solvent includes but is not limited to: isopentane, hexane, heptane, toluene, xylene, naphtha, and mineral oil.
[0034] A fifth object of the present invention is to provide an olefin polymerization catalyst for use in olefin polymerization reactions, specifically, in olefin homopolymerization reactions or copolymerization reactions.
[0035] The catalyst of the present invention is suitable for homopolymerization of various ethylenes or copolymerization of ethylene and alpha-olefins, wherein the alpha-olefin can be selected from one of propylene, butene, pentene, hexene, octene and 4-methylpentene-1. The polymerization process can adopt gas phase method, slurry method and solution method, and is more suitable for gas phase fluidized bed polymerization. The conditions for olefin polymerization can be conventionally selected according to the prior art, and will not be described in detail here.
[0036] The present invention provides a metal-silane composite catalyst, which includes a mixture of components such as diazacyclodialkoxysilane compounds, organic compounds containing CO and / or C=O, metal halides, ultrafine inorganic oxides, and / or their reaction products, and the composite catalyst is used as an olefin polymerization catalyst, and the ultrafine inorganic oxide is used as a carrier, and the organic compound containing CO and / or C=O, magnesium halide, diazacyclodialkoxysilane compounds, and titanium halide are reacted to obtain a mother liquid, which is mixed with the carrier, and finally a catalyst component is obtained by spray molding, and an organic aluminum compound is added to obtain an olefin polymerization catalyst with high activity. The polymer obtained by using the olefin polymerization catalyst has a high melt index, low hexane extract and low oligomer content.
[0037] The diazacyclodialkoxysilane compound used in the present invention is a silane compound containing an alkoxy group, wherein the alkoxy group has a strong electron-donating effect, so that the coordination of the silicon atom with the active center can effectively improve the polymerization efficiency of the active center of the catalyst; moreover, the diazacyclodialkoxysilane compound has a significant steric effect, which can improve the hydrogen sensitivity of the polymerization and improve the catalytic efficiency. In the actual polymerization reaction, it is shown that under the same polymerization conditions, the catalyst system containing the diazacyclodialkoxy group can improve the polymerization activity of the catalyst and the melt index of the prepared polymer while reducing the content of hexane extractables. DETAILED DESCRIPTION
[0038] The present invention is described in detail below in conjunction with specific embodiments. It is necessary to point out that the following embodiments are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by those skilled in the art based on the contents of the present invention still fall within the scope of protection of the present invention.
[0039] The test instruments and test conditions used in the examples are as follows:
[0040] 1. Catalyst activity: expressed as the weight of polyethylene resin obtained per gram of catalyst;
[0041] 2. Polymer melt index (MI): 6932 melt index tester, CEAST, Italy;
[0042] 3. Hexane extractable content in polymer powder (wt%): The dried polymer powder is extracted with hexane, specifically, the polymer is eluted with hexane for 4 hours. The percentage of the weight difference of the polymer powder before and after extraction to the weight of the polymer powder before extraction is the hexane extractable content in the polymer powder.
[0043] 4. Determination of titanium content in catalyst components: The catalyst sample was dissolved in 1M sulfuric acid, the dissolved solution was measured using a spectrophotometer, and the titanium content was calculated using the working curve.
[0044] 5. The content of ultrafine inorganic oxide is obtained by calculating the ratio of feed amount to output catalyst mass.
[0045] The raw materials used in the examples and comparative examples, unless otherwise specified, are disclosed in the prior art, for example, they can be directly purchased or prepared according to the preparation methods disclosed in the prior art.
[0046] Example 1
[0047] (1) Preparation of metal-silane composite catalyst
[0048] 1.5 g TiCl 4 、4.0g anhydrous MgCl 2 , 1.9 g of dipiperidyldiethoxysilane and 100 mL of tetrahydrofuran, raise the temperature to 65° C. with stirring, react at this temperature for 3 hours, and then cool to 35° C. to obtain a mother liquor.
[0049] Into a 250mL three-necked flask purged with nitrogen, 6g of silica gel (Cabot Corporation TS-610, particle size 0.02-0.1μm) was added, and the cooled mother liquor was added. The temperature was maintained at 35°C. After stirring for 1 hour, the mother liquor mixed with silica gel was spray dried using a spray dryer. The spraying conditions were: inlet temperature 195°C, outlet temperature 110°C, to obtain a catalyst component with a titanium content of 2.37wt% and a silicon dioxide content of 23wt%.
[0050] (2) Ethylene slurry polymerization
[0051] 1L of hexane was added to a 2L polymerization kettle purged with nitrogen, and 2mL of 1M triethylaluminum / hexane solution and 0.01g of the metal-silane composite catalyst component obtained in step (1) were added at the same time. The temperature was raised to 75°C and hydrogen was added at 0.18Mpa. After the hydrogenation was completed, ethylene was added at 0.75Mpa. The temperature was raised to 85°C, and the reaction was carried out for 2 hours, and then the temperature was lowered and the material was discharged. The polymerization results are shown in Table 1.
[0052] Example 2
[0053] (1) Preparation of metal-silane composite catalyst
[0054] Same as Example 1.
[0055] (2) Ethylene slurry polymerization
[0056] The same as Example 1, except that 0.05 g of the metal-silane composite catalyst component obtained in step (1) was added, the temperature was raised to 75° C., 0.68 MPa of hydrogen was added, and after the hydrogenation was completed, 0.35 MPa of ethylene was added. The polymerization results are shown in Table 1.
[0057] Example 3
[0058] (1) Preparation of catalyst system
[0059] The same as Example 1, except that the reaction temperature was adjusted to 85° C., the reaction time was adjusted to 4 hours, and the titanium content of the obtained catalyst component was 2.35 wt %, and the silicon dioxide content was 22 wt %.
[0060] (2) Ethylene slurry polymerization
[0061] Same as Example 1, the polymerization results are shown in Table 1.
[0062] Example 4
[0063] (1) Preparation of catalyst system
[0064] The same as Example 1, except that the spray inlet temperature was adjusted to 170°C, the outlet temperature was 100°C, and the titanium content of the obtained catalyst component was 2.25wt%, and the silicon dioxide content was 21wt%.
[0065] (2) Ethylene slurry polymerization
[0066] Same as Example 1, the polymerization results are shown in Table 1.
[0067] Example 5
[0068] (1) Preparation of metal-silane composite catalyst
[0069] The same as Example 1, except that the amount of dipiperidyldiethoxysilane used is 3.8 g, and the titanium content of the obtained catalyst component is 2.45 wt%, and the silicon dioxide content is 24 wt%.
[0070] (2) Ethylene slurry polymerization
[0071] Same as Example 1, except that the metal-silane composite catalyst obtained in step (1) above was added. The polymerization results are shown in Table 1.
[0072] Example 6
[0073] (1) Preparation of metal-silane composite catalyst
[0074] Same as Example 3.
[0075] (2) Ethylene slurry polymerization
[0076] Same as Example 2, except that the metal-silane composite catalyst obtained in step (1) above was added. The polymerization results are shown in Table 1.
[0077] Example 7
[0078] (1) Preparation of metal-silane composite catalyst
[0079] The same as Example 1, except that the amount of dipiperidyldiethoxysilane used is 1.0 g, and the titanium content of the obtained catalyst component is 2.18 wt%, and the silicon dioxide content is 24 wt%.
[0080] (2) Ethylene slurry polymerization
[0081] Same as Example 1, except that the metal-silane composite catalyst obtained in step (1) above was added. The polymerization results are shown in Table 1.
[0082] Example 8
[0083] (1) Preparation of metal-silane composite catalyst
[0084] Same as Example 5.
[0085] (2) Ethylene slurry polymerization
[0086] Same as Example 2, except that the metal-silane composite catalyst obtained in step (1) above was added. The polymerization results are shown in Table 1.
[0087] Example 9
[0088] (1) Preparation of metal-silane composite catalyst
[0089] The same as Example 1, except that dipyrrolyldiethoxysilane is used in place of dipyridyldiethoxysilane in an amount of 0.9 g. The titanium content of the obtained catalyst component is 2.20 wt %, and the silicon dioxide content is 23 wt %.
[0090] (2) Ethylene slurry polymerization
[0091] Same as Example 1, except that the metal-silane composite catalyst obtained in step (1) above was added. The polymerization results are shown in Table 1.
[0092] Example 10
[0093] (1) Preparation of metal-silane composite catalyst
[0094] Same as Example 7.
[0095] (2) Ethylene slurry polymerization
[0096] Same as Example 2, except that the metal-silane composite catalyst obtained in step (1) above was added. The polymerization results are shown in Table 1.
[0097] Embodiment 11
[0098] (1) Preparation of metal-silane composite catalyst
[0099] The same as Example 1, except that dipiperidyldiethoxysilane is replaced by dipiperidyldimethoxysilane in an amount of 0.9 g. The titanium content of the obtained catalyst component is 2.32 wt %, and the silicon dioxide content is 22 wt %.
[0100] (2) Ethylene slurry polymerization
[0101] Same as Example 1, except that the metal-silane composite catalyst obtained in step (1) above was added. The polymerization results are shown in Table 1.
[0102] Example 12
[0103] (1) Preparation of metal-silane composite catalyst
[0104] Same as Example 9.
[0105] (2) Ethylene slurry polymerization
[0106] Same as Example 2, except that the metal-silane composite catalyst obtained in step (1) above was added. The polymerization results are shown in Table 1.
[0107] Comparative Example 1
[0108] (1) Preparation of catalyst components
[0109] 1.5 g TiC1 was added to a 250 mL three-necked flask purged with nitrogen. 4 , 4.0 g anhydrous MgCl 2 and 100 mL of tetrahydrofuran, and heated to 65° C. with stirring, and reacted at this temperature for 3 hours, and then cooled to 35° C. to obtain a mother liquor.
[0110] Into a 250mL three-necked flask purged with nitrogen, 6g of silica gel (Cabot Corporation TS-610, particle size 0.02-0.1μm) was added, and the cooled mother liquor was added, the temperature was maintained at 35°C, and after stirring for 1 hour, the mother liquor mixed with silica gel was spray dried using a spray dryer. The spraying conditions were: inlet temperature 195°C, outlet temperature 110°C, to obtain a catalyst component with a titanium content of 2.2wt% and a silicon dioxide content of 25wt%.
[0111] (2) Ethylene slurry polymerization
[0112] 1L of hexane was added to a 2L polymerization reactor purged with nitrogen, and 2mL of 1M triethylaluminum / hexane and 0.01g of catalyst were added at the same time. The temperature was raised to 75°C and hydrogen was added at 0.18Mpa. After hydrogenation, 0.75Mpa of ethylene was added. The temperature was raised to 85°C, and after reacting for 2 hours, the temperature was lowered and the material was discharged. The polymerization results are shown in Table 1.
[0113] Comparative Example 2
[0114] (1) Preparation of catalyst components
[0115] Same as Comparative Example 1.
[0116] (2) Ethylene slurry polymerization
[0117] The same as comparative example 1, except that 0.05 g of catalyst was added, the temperature was raised to 75° C., 0.68 MPa of hydrogen was added, and 0.35 MPa of ethylene was added after the hydrogenation was completed. The polymerization results are shown in Table 1.
[0118] Table 1. Catalyst performance obtained in Examples and Comparative Examples
[0119]
[0120] It can be seen from the polymerization data in Table 1 that under the same polymerization conditions, compared with Comparative Example 1, the catalysts in Examples 1, 3 to 5, 7, 9 and 11 of the present invention have higher activity and better hydrogen adjustment sensitivity; the resulting polymer has a higher melt index and a lower hexane extractable content. When polymerized under high hydrogen conditions, the resulting resin has a lower molecular weight and is not used to determine the hexane extractables. Under the same high hydrogen conditions, compared with Comparative Example 2, the catalysts in Examples 2, 6, 8, 10 and 12 of the present invention also have higher catalytic activity.
[0121] The embodiments of the present invention have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and changes will be apparent to those skilled in the art without departing from the scope and spirit of the described embodiments.
Claims
1. A metal-silane composite catalyst comprising: A mixture of diazaheterocyclyldialkoxysilane compounds, organic compounds containing CO and / or C=O, metal halides and / or reaction products of the above components, wherein the metal halides include titanium halides and magnesium halides.
2. The metal-silane composite catalyst according to claim 1, characterized in that The general formula of the diazaheterocyclic dialkoxysilane compound is (RO)2Si(NC n H 2n )2, where -NC n H 2n is a nitrogen heterocyclic group, n is an integer of 3 to 10, preferably 4 or 5; R is selected from C1 to C8 alkyl, C2 to C6 alkenyl, C2 to C6 alkynyl, C3 to C10 cycloalkyl or C6 to C12 aryl, preferably C1 to C5 alkyl, C3 to C8 cycloalkyl or C6 to C10 aryl; and / or, The organic compound containing CO and / or C=O is selected from at least one of esters, ethers and ketones, preferably at least one of alkyl esters of C1-C8 saturated fatty carboxylic acids, alkyl esters of C7-C12 aromatic carboxylic acids, C2-C10 fatty ethers, C3-C8 cyclic ethers and C3-C8 saturated fatty ketones; and / or, The magnesium halide is selected from at least one of magnesium chloride, magnesium bromide and magnesium iodide; and / or, The titanium halide is selected from at least one of titanium trichloride, titanium tetrachloride, titanium tribromide and titanium tetrabromide, preferably at least one of titanium trichloride and titanium tetrachloride; and / or, The metal-silane composite catalyst also includes ultrafine inorganic oxides.
3. The metal-silane composite catalyst according to claim 2, characterized in that: The diazaheterocyclyldialkoxysilane compound is selected from at least one of dipiperidyldiethoxysilane, dipiperidyldimethoxysilane and dipyrrolyldiethoxysilane; and / or, The organic compound containing CO and / or C=O is selected from at least one of methyl formate, ethyl formate, isopropyl formate, n-propyl formate, methyl acetate, ethyl acetate, n-propyl acetate, isopropyl acetate, n-butyl acetate, isobutyl acetate, ethyl ether, propyl ether, hexyl ether, tetrahydrofuran, acetone, and methyl isobutyl ketone, preferably at least one of methyl formate, ethyl acetate, n-butyl acetate, ethyl ether, hexyl ether, tetrahydrofuran, acetone, and methyl isobutyl ketone, more preferably tetrahydrofuran; and / or, The ultrafine inorganic oxide is selected from at least one of ultrafine alumina and ultrafine silica, preferably ultrafine silica; and / or, The particle size of the ultrafine inorganic oxide is 0.01 to 10 μm, preferably 0.01 to 5 μm, more preferably 0.01 to 2 μm; and / or, Based on 100 wt% of the total weight of the metal-silane composite catalyst, the ultrafine inorganic oxide is 5-40 wt%, preferably 10-35 wt%, and more preferably 15-30 wt%.
4. The metal-silane composite catalyst according to claim 1, characterized in that Based on the total weight of the metal-silane composite catalyst being 100 wt%, the content of titanium element is 0.2 to 5.5 wt%, preferably 0.5 to 3.0 wt%; and / or, Calculated per mol of titanium element, the diazacyclodialkoxysilane compound is 0.02 to 12 mol, preferably 0.1 to 10 mol, and more preferably 0.1 to 5 mol; the organic compound containing CO and / or C=O is 1 to 550 mol, preferably 25 to 350 mol, and more preferably 120 to 250 mol; the magnesium halide is 0.3 to 12 mol, preferably 1 to 10 mol, and more preferably 1 to 8 mol.
5. A method for preparing the metal-silane composite catalyst according to any one of claims 1 to 4, comprising: The metal-silane composite catalyst is obtained by reacting components including a diazaheterocyclic dialkoxysilane compound, an organic compound containing CO and / or C=O, and a metal halide.
6. The preparation method according to claim 5, characterized in that: The preparation method specifically comprises the following steps: (a) stirring and reacting the components including the diazaheterocyclyldialkoxysilane compound, the organic compound containing CO and / or C=O, the titanium halide and the magnesium halide to obtain a composite catalyst mother liquid; (b) adding ultrafine inorganic oxide to the composite catalyst mother solution and mixing to obtain a slurry; (c) spray drying the slurry to obtain the metal-silane composite catalyst.
7. The preparation method according to claim 6, characterized in that: The reaction conditions in step (a) are: reaction temperature of 55 to 85° C., and / or, reaction time of 2 to 3.5 h; and / or, The content of ultrafine inorganic oxide in the slurry of step (b) is 1 to 45 wt%, preferably 5 to 30 wt%; and / or, The spray drying conditions in step (c) include: an inlet temperature of 90 to 220°C, preferably 110 to 200°C; and / or an outlet temperature of 70 to 110°C, preferably 95 to 110°C.
8. A metal-silane composite catalyst according to any one of claims 1 to 4 or a metal-silane composite catalyst obtained by the preparation method according to any one of claims 5 to 7, for use in preparing an olefin polymerization catalyst.
9. An olefin polymerization catalyst comprising: An organic aluminum compound, and the metal-silane composite catalyst according to any one of claims 1 to 4 or the metal-silane composite catalyst obtained by the preparation method according to any one of claims 5 to 7.
10. The olefin polymerization catalyst according to claim 9, characterized in that The general formula of the organoaluminum compound is A1R n X 3-n , wherein R is a C1-C18 straight or branched alkyl group, X is a halogen, and 0<n≤3; preferably, the organoaluminum compound is selected from at least one of triethylaluminum, triisobutylaluminum, tri-n-hexylaluminum, tri-n-octylaluminum, and diethylaluminum monochloride; and / or, The molar ratio of the aluminum element in the organic aluminum compound to the titanium element in the metal-silane composite catalyst is (3-4500):1, preferably (12-1800):
1.
11. Use of the olefin polymerization catalyst according to claim 9 or 10 in olefin polymerization reaction.
Citation Information
Patent Citations
Catalyst used for ethylene polymerization or copolymerization, its preparation method and application
CN100389134C
Catalyst component for polymerization of ethylene or combined polymerization, producing method and catalyst thereof
CN101173015A
Catalyst component for olefin polymerization reaction, catalyst thereof, and preparation method and application of catalyst
CN112812205A
Catalyst used in olefin polymerization, and component thereof
CN102336847A
Preparation method of catalyst for ethylene polymerization
CN103524643A